Aid Agency Competition : A Century of Entry, But No Exit - Harford, Tim (World Bank, Washington, DC, 2012)
Critics of the aid industry have accused it of acting like a cartel (Easterly 2002). The accusation has some bite-globally the industry remains somewhat concentrated, and for the typical recipient country, highly concentrated. Yet the most striking fact about the industry is how relentlessly competitive pressures are building. There has been a constant stream of new entrants, a steady fall in global and local concentration, and a clear tendency for donors to break out of historical patterns of aid and compete with one another. Could greater competition improve the efficiency of the aid system?